Submucosal injection of dexamethasone and methylprednisolone for the control of postoperative sequelae after third molar surgery: randomized controlled trial. Issue 2 (February 2018) - Chugh, A.; Singh, S.; Mittal, Y.; Chugh, V.
Abstract: Pain, swelling, and trismus are known sequelae of third molar surgery that can significantly affect the individual's quality of life (QOL). These should be minimized to improve QOL. The purpose of this study was to compare the effects of the preoperative submucosal administration of equivalent doses of two commonly used steroids on these postoperative sequelae. A randomized controlled clinical trial was conducted involving 60 subjects requiring the removal of impacted mandibular third molars. Extraction cases with a similar difficulty index were included. The participants were allocated randomly to three groups: the placebo group received normal saline injection (control), while the 8 mg dexamethasone group and 40 mg methylprednisolone group received submucosal injections of these steroids preoperatively. Each participant was assessed for postoperative pain, swelling, and trismus, along with a subjective assessment of QOL through a structured questionnaire. The participants administered dexamethasone showed significant reductions in pain and trismus compared to the control group ( P < 0.05). Submucosal injection of dexamethasone was found to be superior to methylprednisolone only in terms of the reduction in swelling. QOL was minimally affected in patients administered dexamethasone as compared to methylprednisolone and control subjects. The preoperative submucosal use of steroids can be considered an effective, safe, and simple therapeutic strategy to reduce swelling, pain, and trismus after the surgical removal of impacted mandibular third molars.